2022
DOI: 10.17305/bjbms.2022.7675
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive significance of VEGF, CD31, and Ang-1 in patients with metastatic clear cell renal cell carcinoma treated with first-line sunitinib

Abstract: The most common type of renal cell carcinoma (RCC) is clear cell renal cell carcinoma (ccRCC), which has a high metastatic potential. Even though the International Metastatic RCC Database Consortium (IMDC) risk model is conventionally utilized for selection and stratification of patients with metastatic RCC (mRCC), there remains an unmet demand for novel prognostic and predictive markers. The goal of this study was to analyze the expression of Vascular endothelial growth factor (VEGF), Cluster of Differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Unlike ccRCC, where VEGFA overexpression is more prevalent and consistently associated with poorer prognosis ( 37 ), the relationship between VEGF expression and pRCC outcomes appears to be more complex. A study has reported higher VEGF expression in pRCC tumors associated with adverse clinicopathological features, such as larger tumor size, higher stage, and lymph node involvement, suggesting a potential association with aggressive tumor behavior ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ccRCC, where VEGFA overexpression is more prevalent and consistently associated with poorer prognosis ( 37 ), the relationship between VEGF expression and pRCC outcomes appears to be more complex. A study has reported higher VEGF expression in pRCC tumors associated with adverse clinicopathological features, such as larger tumor size, higher stage, and lymph node involvement, suggesting a potential association with aggressive tumor behavior ( 10 ).…”
Section: Discussionmentioning
confidence: 99%